MORAL VALUE AND CHARACTER BUILDING EDUCATION IN FOLKLORE: LUBUK EMAS - Silvania Sefaca Sipahutar; Raees Narhan; Ratna Paramita; Yenita Br Sembiring (PROJECT (Professional Journal of English Education), 2021)
The folklore entitled Lubuk Emas is one of the stories that come from North Sumatra, Indone-sia. The aim of this study is the researcher wants to show the importance of moral value and character-building education through the Lubuk Emas folklore. This research used the library research method, where the researcher will gathering information about the moral value and character-building education through Lubuk Emas folklore.  The results of this study are to show that the character has a different characterization and also give the reader a different mo-rality include individual morality and social morality. Which later can be applied in everyday life through studying the characters so that the children will grow with a commendable person-ality and character. Keywords:  Character Building, Education, Folklore, Lubuk Emas, Moral Value